Dampak Tekanan Akademik Terhadap Kesehatan Mental Siswa dalam Konteks Pendidikan Modern - Sahbuki Ritonga; Elviana Sinaga; Naimah Agustina; Chanra; Azhar (Jurnal Zeniusi, 2025)
This study aims to analyze the impact of academic pressure on students' mental health in a modern, competitive, results-oriented education system. Current education is characterized by high demands, a dense curriculum, and cognitive-based assessment standards, which often neglect students' emotional aspects. The study used a qualitative approach with a descriptive survey method, involving 30 high school students in grades 11 and 12 from three major cities in Indonesia. Data were collected through an open-ended questionnaire and analyzed using thematic analysis techniques. The results showed that the majority of students experienced academic pressure that negatively impacted their mental health, such as stress, anxiety, fatigue, sleep disturbances, and academic burnout. Furthermore, students also found it difficult to manage their time between schoolwork and personal needs. Although some students stated they received support from their schools, most felt that the education system still did not adequately address the balance between academic achievement and mental health. Therefore, a more humane educational policy reform is needed, with an empathetic and responsive approach to students' psychological conditions. This study recommends the importance of integrating mental health support services into the curriculum and learning system in schools